Milk quality characteristics of indigenous sheep breeds Boutsko, Frisarta and Karagouniko - SKOUFOS, I.; GIANNENAS, I.; KARAMOUTSIOS, A.; TSINAS, A.; PAPADOPOULOS, G. K.; TZORA, A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study, the chemical and microbiological characteristics of ovine milk from three indigenous Greek breeds, Boutsko, Frisarta and Karagouniko were examined, while reared in the semi mountainous areas. The milk yield of each sheep breed was recorded at the early, mid and late stages of lactation for two consecutive years. The average composition of the samples of ewe’s milk used in this study was similar for protein, lactose and total solids among the three; however fat values were significantly lower (p<0.05) in Frisarta milk compared to Boutsko and Karagouniko. Total viable cells of Boutsko and Karagouniko raw milk were lower (p<0.05) than those of Frisarta. Enterobacteria detected in bulk raw milk from Boutsko and Frizarta breeds were in lower numbers (p<0.05) compared to milk from Karagouniko breed. Somatic cells were also counted in lower numbers in milk collected from Boutsko and Karagouniko breeds compared to Frisarta. The percentage of detected as potentially pathogenic bacteria (coagulase negative staphylococci and enterobacteriae) was higher in the milk from Frisarta sheep milk.